Context Assessment: Analysis of the biophysical, sociopolitical, economic and agroecological context in Attapeu Province Lao PDR - Clayton, Terry; Douangsavanh, Somphasith; Sinavong, Phonevilay; Phimmachanh, Phoutthasinh; Nhuong, Tran; Kosal, Mam; Dyna, Eam; Viossanges, Mathieu; Dubois, Mark (2023)
The purpose of the Context Assessment is threefold: first, to characterize the location of the ALL, as well as its environmental, social, and economic context; second, to understand the data and information currently available in each ALL, and third to characterize how and the extent to which agroecological principles are already being employed in each ALL. The source of information has been from secondary and primary data. The latter from specific activities that other work packages recently developed. The information in this Context Assessment is seen as a ‘live’ document that will be updated as the activities of all work packages are move forward.